Conferences and Conventions: A Global Industry (Events Management) - Tony Rogers; Peter Wynn-Moylan (New York Routledge, 2023)
Fully revised and updated to reflect current trends and emerging topics, the fourth edition of Conferences and Conventions: A Global Industry provides an expert-led, comprehensive introduction to, and overview of, the key elements of the global conference, convention and meetings industry. This book examines the conference industry's origins, structure and future development, as well as its economic, social and environmental impacts. It provides an in-depth analysis of the strategies, practices, knowledge and skills required to organise memorable conferences and similar business events, with detailed descriptions of all the planning and operational processes. Following an international approach, this edition features additional sections on the increase in technological advancements and opportunities, as well as the rise of virtual and hybrid events in a post-pandemic era. Written in an accessible and engaging style, the book includes integrated case studies to highlight current issues and demonstrate theory in practice. Structured logically with useful features throughout to aid learning and understanding, this book is an invaluable resource to students following events management, hospitality and tourism courses, as well as for event planners and practitioners already working in the conference industry.
Keywords: Events management; Conferences; Conventions; Industry; (ETB-2003) Conference and Events Management